Four Important Managerial Competencies For Middle Managers As Policy Drafter (A Study of ones of the ministries middle managers as policy drafter) - Danny Zulkarnaen; R. Madhakomala; Mukhtadi (Journal of Business and Behavioural Entrepreneurship, 2020)
This study is aimed to identified of important managerial competencies of middle managers as chairperson of the policy drafter through integrity, cooperation, communication, and goal orientation. This research was conducted qualitatively using the phenomenology method approach. Data was collected through questionnaires, observations, and in-depth interviews from selected respondents. The result shows a level of mastery, and most respondents agreed upon integrity (50%), cooperation (45%), communication (50%), and goal orientation (50%) are important managerial competencies as chairperson. The result of this study is useful for public service middle managers